Assessment of using ponds as a nature-based solution on the optimal irrigation management of paddy fields - Somaye Janatrostami (Water Supply, 2024)
The water availability to supply agricultural water requirements plays an important role in the performance of agricultural products. Paddy fields depend heavily on water during cultivation, making this issue particularly important. In such cases, nature-based solutions, such as ponds, can be a suitable method to address water shortages for irrigation purposes. This study aims to develop a water allocation optimization model to evaluate the impact of two scenarios in ponds. In the scenario of increasing the ponds' depth, the hydraulic connection between the ponds and the groundwater level was taken into consideration. Based on this perspective, the scenario of increasing the depth resulted in a 0.33 million m3 increase in the volume of ponds, leading to an average percentage increase of 0.23% in the supply of irrigation requirements. The optimized model results in the pond dredging scenario showed a 2.03 million m3 increase in the volume of available water compared to the existing conditions, and a 1.70 million m3 increase compared to the pond deepening scenario. The results show that dredging ponds have a greater impact on increasing available water volume. It is also important to consider the hydraulic connection between ponds and groundwater levels in the pond-deepening approach. HIGHLIGHTS Evaluating two scenarios: increasing pond depth by deepening and improving pond efficiency by dredging.; Considering the hydraulic connection between ponds and the groundwater level in the adjacent aquifer in the deepening scenario.; In the study area, dredging to enhance the pond efficiency had a greater effect on increasing the available water volume.;